EFL Learners’ Attitude towards Teacher’s and Peers’ Written Corrective Feedback - Hartono Hartono; Jarum Jarum; Khoiriyah Khoiriyah (VELES Voices of English Language Education Society, 2023)
This research was aimed at revealing EFL learners’ attitude toward their teacher’s and peers’ written corrective feedback (WCF) on their composition in the context of teaching and learning English as a foreign language (EFL). Fifty-nine students were involved in this research. The questionnaire on a three-point Likert scale – showing options of agree, neutral, and disagree – was used to collect the research data. Further, the result of data analysis showed that: (1) the learners generally showed positive attitude toward both the teacher’s and peers’ WCF; (2) they felt challenged and encouraged when their teacher or their peers always corrected the errors they had made in their composition; (3) they indicated more positive attitude toward direct than toward indirect WCF; (4) they expected their most frequent errors in their composition to be corrected; (5) they preferred their global errors to be corrected than their local errors.; and (6) they preferred their errors to be corrected by their teacher than by their peer. Based on the findings, it can then be concluded that WCF is generally needed by EFL learners when learning to write composition. It needs to be provided with such considerations as what types of correction techniques are used (direct and/or indirect), which errors are prioritized to correct (the most frequent); and who should correct the errors (teachers are preferred against peers).